Dasar Keilmuan Bimbingan Konseling dalam Perspektif Filsafat Ilmu (Ontologi, Epistimologi dan Aksiologi dalam Bimbingan Konseling) - Bunda, Indah Permata; Sufyarma, Sufyarma; Karneli, Yeni (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to explore the scientific foundation of counseling guidance from the perspective of the philosophy of science, focusing on three main aspects: ontology, epistemology, and axiology. In the ontology study, this research analyzes the nature and existence of entities that are the objects of counseling guidance, such as individuals, psychological issues, and the process of behavioral change. Epistemology in counseling guidance examines how knowledge about counseling is acquired, validated, and applied, encompassing the scientific approaches, theories, and practices used by counselors. The axiological aspect examines the ethical values and objectives underlying the practice of counseling guidance, including the role of moral values, professional ethics, and the social impact of counseling. This research uses a qualitative approach with literature analysis as the main method. The results indicate that the scientific foundation of counseling guidance is greatly influenced by an ontological understanding of humans as complex and dynamic beings, an interdisciplinary epistemological approach, and an axiological commitment to individual and community well-being